Methodology for information and technologigy assessment of public passenger transport work - A. A. Guskov; N. Y. Zalukaeva; M. A. Sevostyanov (Вестник СибАДИ)
Introduction. The problems of the organisation of urban passenger transportation are considered. The reasons for the inefficient operation of public transport in the cities of Russia and abroad, as well as the factors contributing to this, are investigated. The insufficient level of information technology systems and technologies use in the transportation process is indicated. The purpose of the work is to develop a refined methodology for evaluating the efficiency of public passenger transport based on the criteria of the information technology indicator, as well as to test the evaluation of the efficiency of motor transport enterprises engaged in passengers transportation in Tambov according to this indicator.Materials and methods. A refined methodology for evaluating the efficiency of public passenger transport has been developed based on the criteria of the information technology indicator. Each criterion was assigned a weighting indicator (coefficient), depending on the significance and impact on the efficiency and safety of public passenger transport.Results. The study of the efficiency of public passenger transport in Tambov according to the criteria of information technology assessment showed that, in general, the level of equipment is lower than the average estimated indicator - from 5.55 to 8.3 points. This indicates the insufficient equipment of carriers with information technologies and systems.Discussion and conclusion. The measures to improve the efficiency of public passenger transport are proposed.